The Tale of the German Gas Price Brake: Why We Need Economic Disaster Preparedness in Times of Overlapping Emergencies - Isabella Weber; Thore Beckmann; Jan-Erik Thie (Intereconomics, 2023)
The gas price shock has been a major contributor to inflation in Germany. In this context, Dullien and Weber (2022a, b, c) proposed a two-tier pricing scheme for natural gas in the spring of 2022 that lowers the price for a base quota through a subsidy while maintaining high market prices on the margin. In response to the war in Ukraine, the German government acted swiftly to try to access new sources of gas supply. However, it was not until September that the government decided to dampen the effects of the gas price shock and initiated the so-called "gas price brake" that implements such a two-tier system. In this article, we argue that the gas price brake makes a critical contribution towards providing relief for households, and alleviates cost pressure on firms while retaining incentives for consumers and businesses to save gas. It is also an important measure for macroeconomic stabilisation and marks a breakthrough in the policy approach to price shocks in systemically significant sectors. The gas price brake establishes that targeted price stabilisation can be an important tool for governments in times of emergencies. Yet, the delay in responding to the price shock meant that the speed of policy implementation had to take priority over everything else and that help came at a time when the shock had already percolated through the whole economy. Our times of overlapping emergencies require disaster preparedness in economic policymaking for governments to be able to react to sectoral shocks without delay (Weber et al., 2022).
Keywords: D47; E31; O13; 330; natural gas market; gas price; price regulation; Germany; Erdgasmarkt; Gaspreis; Preisregulierung; Deutschland